The vascular anatomy of the lower abdomen, pelvis and upper hindleg in Procavia capensis - Swart, P. S.(Paul Stephanus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1966.